Abusive leadership: A moderated-mediation through leader-member exchange and by organizational politics - Drory, Amos; Shkoler, Or; Tziner, Aharon (Frontiers in Psychology, 2022)
Abusive leadership has been shown to have adverse consequences for both the employees and the organization. In the current paper, the impacts of such a leadership style on workers’ turnover intentions (TIs), counterproductive work behaviors (CWBs) and organizational citizenship behaviors (OCBs) are investigated through a dyadic lens—the mediation of leader-member exchange (LMX). Furthermore, when the workplace atmosphere is also tainted by high level of perceived organizational politics (POP) (as a moderator), these relationships deepen and and/or change (for the worse). To test the moderated-mediation research model, an online sample of 619 participants was obtained. The results support an interesting moderated-mediation of LMX by POP. Theoretical and practical implications, limitations and future research suggestions are discussed.